Evaluation of patient safety culture in community pharmacies in Qatar - Yaw B. Owusu (17380354) (2021)
Introduction Patient safety culture is a key contributor to medication safety globally. However, the perspective of pharmacists and other personnel in community pharmacy regarding patient safety culture may vary from one country to another. Objective The aim of this study was to determine the perspectives of community pharmacy personnel in Qatar about patient safety culture in community pharmacy setting. Methods A cross-sectional web-based survey utilising the Agency for Healthcare Research and Quality Community Pharmacy Survey on Patient Safety Culture was conducted. Participants included community pharmacy personnel practicing in Qatar. Both descriptive and inferential statistics were applied for data analyses, with statistical significance set at ≤ 0.05. Results Two hundred and forty participants completed the survey. A large proportion of the respondents (52.5%) reported an “excellent” overall rating of patient safety in their respective community pharmacies. Patient counselling and teamwork composites of patient safety culture were associated with the highest positive responses (95% and 93.7%, respectively). The “staffing, work pressure and pace” composite demonstrated the lowest positive response (50.6%) among the 11 composites. Inferential analysis revealed that working in chain pharmacies was significantly associated with positive responses related to “teamwork” (P = .019). Furthermore, working for more than 40 hours per week had a significant positive influence on the overall perceptions of patient safety (P = .025). Conclusion There was an overall positive perception towards patient safety culture among the surveyed community pharmacy personnel in Qatar. Superiority was observed with patient counselling and teamwork, while staffing, work pressure and pace were judged poorly, warranting further investigations and potential targeting for interventions. Other Information Published in: International Journal of Clinical Practice License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/ijcp.14055